Pengembangan Objek Wisata Tongkonan Karuaya Di Lembang Tumbang Datu Kecamatan Sangalla’ Utara - Arun Ayun; Debin Palute; Evans Bandaso; Vicky Kurniawan Sakkung; Abedneigo Carter Rambulangi (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Tourism villages have become a major concern in efforts to develop local economies and preserve culture in many regions. Tongkonan Karuaya is one of the tourist attractions in Lembang Tumbang Datu. Visitors can use this area to get to know the typical Toraja customs and culture. This article aims to analyze the development of the Karuaya tourist attraction as a potential tourist destination to support the local economy. The research method used is a qualitative approach by collecting data through interviews, field observations and analysis of related documents. The research results show that the Karuaya tourist attraction has a variety of attractions and cultural heritage. However, challenges such as limited facilities, lack of promotion and the need for infrastructure improvements still need to be addressed. This research underlines the importance of collaboration between local communities and the private sector to optimize the potential of the Karuaya tourist attraction as a sustainable economic resource and utilizing technology such as social media can be an effective tool for introduce the Tongkonan Karuaya tourist attraction to a wide audience, increase its attractiveness, and improve.